Development and Usability of the Specific Heat Capacity Application Kit Among Form 4 Students - Mat Nawi, Mohd Norzaidi (Physics Education Research Journal, 2023)
This study aims to develop an application kit for the specific heat capacity subtopic of the topic of heat and assess the degree of usefulness of the application kit for specific heat capacity among form four students in Malaysia. This development design study based on constructivism theory uses the ADDIE model. A total of 36 Form 4 students were chosen as research participants using a simple random sample procedure to assess the usability level of the application kit. The study tool utilized is a 4-point Likert scale expert validity assessment form and a research question form on the usability of the Specific Heat Capacity Application Kit. The expert approval percentage approach is used to assess expert validity. The Cronbach Alpha reliability coefficient was calculated using the Statistical Package for the Social Sciences (SPSS) software, and the data for the usability study questions were analyzed using descriptive statistical analysis to determine the mean value and standard deviation. The study's findings revealed that the expert approval value for the application kit and instrument was high, with 95.5% and 97.5%, respectively. It received a high dependability rating of 0.82 for the research instrument. The findings also revealed that the application kit is entirely usable (M = 3.84, SP = 0.36). As a result, this application kit is appropriate for use as teaching and learning material for the Form 4 subtopic of specific heat capacity. This application kit will aid in the development of a more active and two-way learning environment between the learner and the instructor, as well as improve the learner's comprehension of the Specific Heat Capacity subtopic.